| 52 | $\partial_t T = \frac{\kappa_\parallel}{\lambda+1} \left [ \left ( \partial_i n b_i b_j \right ) \partial j \left ( \left ( \phi - \psi \lambda \right ) T^{\lambda+1} + \psi \left ( \lambda + 1 \right ) T^{\lambda} T' \right ) + n b_i b_j \left ( \left ( \phi - \psi \lambda \right ) \partial_i \partial_j T^{\lambda+1} + \psi \left ( \lambda + 1 \right ) \partial_i \partial_j T^{\lambda} T' \right ) \right ]$ |
| 53 | |
| 54 | |
| 55 | Now if we write the equation as |
| 56 | |
| 57 | $\partial_t T = B_i \partial_j T^{\lambda+1} + C_j \partial_j T^\lambda T' + D_{ij} \partial_i\partial_j T^{\lambda+1} + E_{ij} \partial_i \partial_j T^\lambda T'$ |
| 58 | |
| 59 | we get expressions for |
| 60 | |
| 61 | $B_j = \frac{\kappa_\parallel \left ( \phi-\psi\lambda \right )}{\lambda+1} \partial_i n b_i b_j $ |
| 62 | |
| 63 | $C_j = \kappa_\parallel \psi \partial_i n b_i b_j $ |
| 64 | |
| 65 | $D_{ij}=\frac{\kappa_\parallel \left ( \phi-\psi\lambda \right )}{\lambda+1} n b_i b_j $ |
| 66 | |
| 67 | $E_{ij} = \kappa_\parallel \psi n b_i b_j $ |
| 68 | |
| 69 | We then need expressions for |
| 70 | |
| 71 | $ \partial_t T = \frac{T'_0 - T_0}{\Delta t}$ |
| 72 | $ \partial_j T^{\lambda+1} = \frac{T^{\lambda+1}_{\hat{j}} - T^{\lambda+1}_{-\hat{j}}}{2 \Delta x}$ |
| 73 | |
| 74 | $ \partial_j T^{\lambda}T' = \frac{T^{\lambda}_{\hat{j}}T'_{\hat{j}} - T^{\lambda}_{-\hat{j}}T'_{-\hat{j}}}{2 \Delta x}$ |
| 75 | |
| 76 | $\partial_i\partial_j T^{\lambda+1} = \frac{T^{\lambda+1}_{\hat{i}+\hat{j}} - T^{\lambda+1}_{\hat{i}-\hat{j}}-T^{\lambda+1}_{-\hat{i}+\hat{j}} + T^{\lambda+1}_{-\hat{i}-\hat{j}}}{4 \Delta x^2}\left(1-\delta_{ij}\right ) + \frac{T^{\lambda+1}_{\hat{i}} - 2T^{\lambda+1}_{0} + T^{\lambda+1}_{-\hat{i}}}{\Delta x^2}\delta_{ij}$ |
| 77 | |
| 78 | $\partial_i\partial_j T^{\lambda}T' = \frac{T^{\lambda}_{\hat{i}+\hat{j}}T'_{\hat{i}+\hat{j}} - T^{\lambda}_{\hat{i}-\hat{j}}T'_{\hat{i}-\hat{j}}-T^{\lambda}_{-\hat{i}+\hat{j}}T'_{-\hat{i}+\hat{j}} + T^{\lambda}_{-\hat{i}-\hat{j}}T'_{-\hat{i}-\hat{j}}}{4 \Delta x^2}\left(1-\delta_{ij}\right ) + \frac{T^{\lambda}_{\hat{i}}T'_{\hat{i}} - 2T^{\lambda}_{0}T'_{0} + T^{\lambda}_{-\hat{i}}T'_{-\hat{i}}}{\Delta x^2}\delta_{ij}$ |
| 79 | |
| 80 | We can also write the equation as |
| 81 | |
| 82 | $\alpha_0 T'_0 + \displaystyle \sum_{\pm i} \alpha_{\pm i} T'_{\pm \hat{i}} + \sum_{\pm i, \pm j,|i| \ne |j|} \alpha_{\pm i, \pm j} T'_{\pm \hat{i} \pm \hat{j}} = \beta$ |
| 83 | |
| 84 | and then work out the coefficients for the matrix equation |
| 85 | |